Tantangan Anak Berkebutuhan Khusus (ABK) Dalam Menjalankan Pendidikan Inklusi di Tingkat Sekolah Dasar - Melati Ansa Purri; Andini Andini; Ulfa Zahra Tunnur; Opi Andriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Students with special needs who study in general elementary schools often face difficulties in thelearning process. Many things become obstacles in the implementation of inclusive education. Thisstudy aims to analyze the implementation of inclusive education for children with special needs inelementary schools. The research method or approach in this study uses a library research approach.Techniques for collecting data and information through literature review. The results of the studystated that formal elementary schools provide inclusive education for Children with Special Needs (ABK). However, when viewed from the level of readiness, it is still not optimal because there is still alack of adequate educators related to their educational background so that in conducting guidance tochildren with special needs, they still encounter many challenges and obstacles. Based on an analysisof several related research journals, it can be said that in fact the special assistant teachers for ABK with an undergraduate background in the Special Education Study Program are still relatively few. Inthe end, most schools that run inclusive education implement the obligation of mentoring training forstudents with Special Needs (ABK).